Archaeometric study of ceramic samples from the peruvian amazon, chronology-stylistics and cultural dynamics - Mujica Baquerizo, Ana Clemencia (2021)
Archaeometry is applied to analyze archaeological ceramics in the Peruvian Amazon. This scientific method allows us to identify its chemical and mineralogical components, just as the raw materials used to produce ceramics. At the same time, it gives us directions about the geographical location of the quarries. The archaeometric analysis let us verify that tempers or organic origin degreasers, as ‘apacharana’ or ‘cauchi’ water sponge, used by Amazonian natives, could have a high mineralogical percentage of aluminosilicates. This research corroborates several hypotheses about mineralogical components in the ceramic making process and other social aspects about chronology and dynamics of interaction processes between prehistoric Amazonian societies.